The effect of plyometric complex training on lower-limb explosive power in adolescents: a systematic review and meta-analysis - Zhang, Jie; Wu, Xiuling; Ye, Xing (Frontiers in Physiology, 2025)
ObjectiveIn this meta-analysis, we aimed to examine the effects of plyometric complex training (PT) on lower-limb explosive power in adolescents and explore the moderating role of different training variables.MethodsEight databases, including CNKI, PubMed, and Web of Science, were systematically searched. Studies were screened according to predefined inclusion, exclusion, and quality assessment criteria. Data were analyzed using STATA 17.0 and Review Manager 5.4.ResultsA total of 11 studies involving 311 participants were included. The meta-analysis showed that PT significantly improved countermovement jump (CMJ) height (MD = 2.20, 95% CI: 1.46–2.95, P < 0.00001) and squat jump (SJ) height (MD = 2.13, 95% CI: 1.32–2.94, P < 0.00001). For sprint performance, PT yielded significant improvements in 20-m sprint time (MD = −0.10, 95% CI: 0.18 to −0.01, P < 0.05), whereas the improvement in 10-m sprint performance was not statistically significant. Subgroup analysis indicated that an intervention duration of ≥8 weeks was a key factor for achieving significant effects.ConclusionPT is useful in improving lower-limb explosive power in teenagers. For the best results, training programs should consider adolescents’ physiological characteristics and use protocols that run for at least 8 weeks, with 2–3 sessions each week, each lasting 20 min–30 min and separated by 1 min–2 min of rest between the sets. The emphasis should be on increasing the jumping ability and short-distance sprint performance.Systematic Review registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, identifier CRD420251149485.